2019
DOI: 10.3389/fnmol.2019.00216
|View full text |Cite
|
Sign up to set email alerts
|

T Cells as an Emerging Target for Chronic Pain Therapy

Abstract: The immune system is critically involved in the development and maintenance of chronic pain. However, T cells, one of the main regulators of the immune response, have only recently become a focus of investigations on chronic pain pathophysiology. Emerging clinical data suggest that patients with chronic pain have a different phenotypic profile of circulating T cells compared to controls. At the preclinical level, findings on the function of T cells are mixed and differ between nerve injury, chemotherapy, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 156 publications
(278 reference statements)
5
82
1
Order By: Relevance
“…The blockade of TNF with etanercept delivered by intrathecal or systemic routes was able to reverse the persistent nociception evoked by TNF in the DRG. It has been demonstrated that T cells may be involved in the transition from acute to chronic pain after inflammatory stimulus, indicating a role in pain maintenance of several inflammatory diseases (45). However, in our model, the number of mononuclear cells, which includes monocytes and lymphocytes, present after AIA did not differ from the basal level of cells from cavities injected with PBS.…”
Section: Discussioncontrasting
confidence: 71%
“…The blockade of TNF with etanercept delivered by intrathecal or systemic routes was able to reverse the persistent nociception evoked by TNF in the DRG. It has been demonstrated that T cells may be involved in the transition from acute to chronic pain after inflammatory stimulus, indicating a role in pain maintenance of several inflammatory diseases (45). However, in our model, the number of mononuclear cells, which includes monocytes and lymphocytes, present after AIA did not differ from the basal level of cells from cavities injected with PBS.…”
Section: Discussioncontrasting
confidence: 71%
“…Changes in predicted blood cell counts were also found in the FM dataset, in which we observed a decrease in predicted CD4+ naive cells in patients and an inverse association between CD8+ T cells and NK cells and the severity of the disease symptoms, assessed as BPI_interference and PCS. Collectively, these results sustain the role of the immune system in painrelated conditions (88).…”
Section: Discussionsupporting
confidence: 64%
“…As such, proliferation and activation of immune cells may be accompanied with increased expression of opioid receptors while the toxic effects of inflammatory and oxidative stress mechanisms may damage cell membranes thereby increasing shedding of the opioid receptors into the plasma. Some T-cell subsets release cytokines and EOS peptides/receptors that can promote, suppress, or resolve pain [60,61]. Moreover, also endomorphin 2 may be produced by immunocytes in inflamed subcutaneous tissues, whereas this peptide is almost absent in non-inflamed tissue [62].…”
Section: Discussionmentioning
confidence: 99%